The Relationship Between Diversity and Abundance of Food Plants and the Diversity and Abundance of Butterflies in Kerandangan Nature Tourism Park - Baiq Giri Larasati Putri; I Putu Artayasa; Gde Cahyadi Wirajagad (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Butterflies are important bioindicators and pollinators whose presence is strongly associated with the availability of food plants and habitat conditions. This study aimed to analyze the relationship between food plant diversity and butterfly diversity in Taman Wisata Alam Kerandangan, West Lombok. The research was conducted in three observation blocks, namely utilization, protection, and rehabilitation, using a survey method along transects. Data were collected on the diversity and abundance of food plants and butterflies, and analyzed using the Shannon-Wiener diversity index and Pearson Product Moment correlation. The results showed that food plants consisted of 1,298 individuals belonging to 27 species and 16 families, with an H’ value of 2.591; the dominant family was Rubiaceae, and the most abundant species was Clerodendrum paniculatum. Butterflies were recorded at 687 individuals, comprising 35 species and 3 families, with an H’ value of 3.183; the dominant family was Nymphalidae, and the most abundant species was Catopsilia pamona. The correlation analysis showed a very weak but positive relationship between food plant diversity and butterfly diversity (r = 0.028), while the relationship between food plant abundance and butterfly abundance was positive and very strong (r = 0.972). These findings indicate that butterfly occurrence in the study area is more strongly influenced by food plant abundance than by food plant diversity.